The Effect of Number of Leaves Leaved on the cuttings and Depth of planting on Rooting Percentage of olive variety (Al-Qaisi) in controlled conditions (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
Olive is one of the plants that have a great variation between the varieties in the ability to root, and the local cultivar (Qaisi) is important Syrian varieties, especially in the inland areas. The vegetative propagation method in by softwood cuttings is the most widely adopted and used method for the propagation of various olive varieties. In this study, the factors affecting the rooting of the local variety (Qaesi), which has some difficulties in rooting, were investigated in order to determine the optimal factors that allow to obtain the highest possible rooting percentage for this variety. The experiments were carried out in the glass house of the Arab Center for Agricultural Research in the Dry Areas (ACSAD) under tight environmental conditions and suitable for rooting the softwood cutting. The cuttings was taken in 2018 (autumn season, spring season) and the effect of the number of leaves left on the cutting was studied (0,1,2,4,6) and The effect of planting depth in the medium (4,6,8) cm on the rooting ratio, the results taken after three months of planting showed that the highest rooting rate was recorded in the autumn season when leaving four leaves by Rooting (80%), the results also showed that the optimal planting depth is 6 cm (immersion half of the cutting in the planting medium) by rooting (55%) during the same season. يعتبر الزيتون من النباتات التي لديها تباين كبير بين الأصناف في القدرة على التجذير, ويعد صنف الزيتون القيسي من الأصناف السورية الهامة ,وخاصة ضمن المناطق الداخلية. وتعتبر طريقة الاكثار الخضري بالعقل الغضة الطريقة المعتمدة والاكثر انتشاراً واستخداماً لإكثار أصناف الزيتون المختلفة . في هذه الدراسة تم البحث في العوامل المؤثرة على تجذير الصنف المحلي (القيسي )الذي يواجه بعض الصعوبات في تجذيره ,بهدف تحديد العوامل المثلى التي تسمح بالحصول على أعلى نسبة تجذير ممكنة لهذا الصنف .  تم تنفيذ التجارب في البيت الزجاجي التابع للمركز العربي لدراسات المناطق الجافة والأراضي القاحلة (اكساد) ضمن ظروف بيئية محكمة وملائمة لتجذير العقل الغضة .تم أخذ العقل في عام 2018 (موسم خريفي , موسم ربيعي) وتم دراسة تأثير عدد الأوراق المتروكة على العقلة (0,1,2,4,6)ورقة ,وتأثير عمق الزراعة ضمن الوسط (4,6,8)سم على نسبة التجذير, وقد بينت النتائج التي أخذت بعد ثلاثة أشهر من الزراعة أن أعلى نسبة تجذير سجلت في الموسم الخريفي عند ترك أربع أوراق بنسبة تجذير (80%),كما أظهرت النتائج أن عمق الزراعة الأمثل هو 6سم (غمر نصف العقلة ضمن الوسط الزراعي) بنسبة تجذير(55%) خلال نفس الموسم.